Money Management Skills of People Amidst the Pandemic - Aggarwal, Meghna; Nidhi; Tyagi, Nupur (Journal of Commerce and Trade, 2021)
The pandemic outbreak has made a lasting effect on the mental and emotional well-being of the individuals and unfortunately, for a few of them, on their physical well-being too. This has caused people to approach their savings and expenditure differently. The adversities ascribed to the pandemic have brought to the fore the inadequate money management skills of the concerned and has also given an insight into the financial lessons learned by them for the unseen future. An online survey was conducted for a week that drew 203 responses from persons of different age groups – young, middle-aged, and retired – who were either salaried or self-employed. Responses for five questions were sought from the respondents and they were given an option to provide multiple responses for each question. This paper highlights the essential outcome and the collective prudence attained through this survey. For some respondents, the pandemic taught them the value of time along with physical and mental wellness which can enhance the quality of their life. This pandemic has made us learn to live every day and feel grateful. Money is not everything. Contradictorily, money is everything in the physical world we are living in, as money is the only source for buying precious items like Remdesivir in Covid. Classification-JEL : E51, I18, J24